Secretory leukocyte protease inhibitor gene deletion alters bleomycin-induced lung injury, but not development of pulmonary fibrosis - Habgood, Antony; Tatler, Amanda L.; Porte, Joanne; Wahl, Sharon, M.; Laurent, Geoffrey, J.; John, Alison, E.; Johnson, Simon, R.; Jenkins, Gisli (Nature Publishing Group, 2016)
Idiopathic pulmonary fibrosis is a progressive, fatal disease with limited treatment options. Protease-mediated transforming growth factor-β (TGF-β) activation has been proposed as a pathogenic mechanism of lung fibrosis. Protease activity in the lung is tightly regulated by protease inhibitors, particularly secretory leukocyte protease inhibitor (SLPI). The bleomycin model of lung fibrosis was used to determine the effect of increased protease activity in the lungs of Slpi− / − mice following injury. Slpi− / −, and wild-type, mice received oropharyngeal administration of bleomycin (30 IU) and the development of pulmonary fibrosis was assessed. Pro and active forms of matrix metalloproteinase (MMP)-2 and MMP-9 were measured. Lung fibrosis was determined by collagen subtype-specific gene expression, hydroxyproline concentration, and histological assessment. Alveolar TGF-β activation was measured using bronchoalveolar lavage cell pSmad2 levels and global TGF-β activity was assessed by pSmad2 immunohistochemistry. The active-MMP-9 to pro-MMP-9 ratio was significantly increased in Slpi− / − animals compared with wild-type animals, demonstrating enhanced metalloproteinase activity. Wild-type animals showed an increase in TGF-β activation following bleomycin, with a progressive and sustained increase in collagen type I, alpha 1 (Col1α1), III, alpha 1(Col3α1), IV, alpha 1(Col4α1) mRNA expression, and a significant increase in total lung collagen 28 days post bleomycin. In contrast Slpi− / − mice showed no significant increase of alveolar TGF-β activity following bleomycin, above their already elevated levels, although global TGF-β activity did increase. Slpi− / − mice had impaired collagen gene expression but animals demonstrated minimal reduction in lung fibrosis compared with wild-type animals. These data suggest that enhanced proteolysis does not further enhance TGF-β activation, and inhibits sustained Col1α1, Col3α1, and Col4α1 gene expression following lung injury. However, these changes do not prevent the development of lung fibrosis. Overall, these data suggest that the absence of Slpi does not markedly modify the development of lung fibrosis following bleomycin-induced lung injury.